Kinematic Alignment May Reduce Opioid Consumption and Length of Stay Compared to Mechanically Aligned Total Knee Arthroplasty. Issue 2 (29th November 2022) - Lung, Brandon E.; Donnelly, Megan R.; McLellan, Maddison; Callan, Kylie; Amirhekmat, Arya; McMaster, William C.; Yang, Steven; So, David H.
Abstract : Objective: Previous studies have sought to determine the effects of total knee arthroplasty (TKA) using kinematic alignment (KA) versus mechanical alignment (MA) to reproduce the native knee alignment and soft tissue envelope for improved patient satisfaction. There are limited studies that compare acute perioperative outcomes between KA and MA patients as it pertains to pain‐related opioid consumption and hospital length of stay (LOS). This study aims to compare early KA and MA in restoring function and rehabilitation after surgery to reduce hospitalization and opioid consumption. Methods: A retrospective review of 42 KA and 58 MA primary TKA patients performed by a single surgeon between 2020–2021 was conducted. Demographics were controlled between groups and radiographic measurements and functional outcomes were compared. Pain was evaluated with inpatient/outpatient morphine milligram equivalents (MME) and visual analogue scale (VAS) scores. Mobility was assessed using multiple measures by a physical therapist. Mean preoperative and 3‐month postoperative flexion range of motion (ROM) were analyzed, and overall complications, LOS, and non‐home discharge between groups compared. Continuous variables were compared using the Wilcoxon rank‐sum test, and categorical variables were compared using the chi‐square or Fisher exact test. Statistical significance was set at P  < 0.05. Results: KA patients had shorter LOS (1.8 vs 3.1 days) and less cumulative opioid requirements compared to MA patients (578 vs 1253 MME). On postoperative day 0, KA patients ambulated on average twice the distance of MA patients (20 vs 6.5 feet). KA patients had residual tibia component in varus (1.4° vs −0.3°), femoral component in valgus (−1.9° vs 0.2°), and valgus joint line obliquity compared with MA (−1.5° vs 0.2°). There were no significant differences between 3‐month postoperative flexion arc motion, discharge destination, KOOS or SF‐12 outcomes, and surgical complication rates between groups. Conclusions: By restoring the native joint line obliquity and minimizing the frequency of ligament releases, KA for TKA may improve pain relief, early mobility, and decreased length of stay compared with traditional methods of establishing neutral limb axis by MA. Abstract : By restoring the native joint line obliquity and minimizing the frequency of ligament releases, kinematic alignment for total knee arthroplasty may decrease length of stay, improve pain relief, and hasten early mobility compared with traditional methods of establishing neutral limb axis by mechanical alignment.